1289 An ergonomist in a continuous improvement team. lessons learned from the aviation maintenance industry. (24th April 2018) - Carmo, J; Lima, M
Abstract : Introduction: The field of ergonomics and the field of quality have a history as two separate disciplines. Both fields are relatively young and are largely of an applied nature. The dominating paradigms have undergone changes in recent years. On the other hand, Health and Safety has its own place, centred in the improvement of working conditions. At TAP PORTUGAL, these three domains are organised in such a way that the ergonomics interventions are embedded in the Occupational Health and Safety department, at UCS, the healthcare provider for all the TAP group companies. One of these companies is the maintenance unit, a MRO, TAP Maintenance and Engineering that plans each year, two Continuous Improvement Weeks and recently the ergonomist has been invited to collaborate. Methods: The ergonomist was invited to participate in three Continuous Improvement Weeks, part of a multidisciplinary team (4 elements) with workers and engineers. The projects were: 'Redesign of a Coffee Machines Test Bench'; 'Brake parts transportation cart' and 'Maintenance aircraft lighting'. The ergonomic analysis methodologies were applied as well as the tools of continuous improvement, requiring an effort of adaptation between the professional different points of view. Results: Both Quality and Ergonomics tools were applied and the teams produced recommendations regarding performance and health and safety concerns. Discussion: The introduction of an ergonomist in the team of continuous improvement improves the final result of the process since the importance of the human factor is determinant for the success of the projects. In order to participate in these teams the ergonomist needs to master the Quality analysis tools, to have the time to carry out the work activity analysis and to obtain information (especially KPI) of both ergonomics and health and safety domains.